Photonics and Optoelectronics: Pioneering Applications in Communication and Computing - Chauhan, Sikha (Journal of Advanced Research in Electronics Engineering and Technology; Vol 11 No 2 (2024): Journal of Advanced Research in Electronics Engineering and Technology, 2024)
Photonics and optoelectronics have played a pivotal role in shaping the future of modern communication and computing systems, enabling transformati ve advancements in areas such as high-speed data transmission, energy-effi cient devices, and the development of integrated circuits. These technologies exploit the unique properti es of light, including its high speed, low loss, and potenti al for parallelism, to create systems that are not only faster but also more reliable and powereffi cient compared to traditi onal electronic systems. This review delves into recent developments in photonics and optoelectronics, examining their profound impact on various domains such as communicati on networks, quantum computi ng, and integrated photonic circuits. Special att enti on is given to key innovati ons in optoelectronic components like lasers, photodetectors, modulators, and photonic integrated circuits (PICs), which are fundamental in achieving breakthroughs in both communicati on and computati on. Moreover, light-based processing and the synergy between photonics and traditi onal electronics are explored as driving forces behind next-generati on computi ng architectures, such as opti cal computi ng and quantum systems. The review also addresses the current research trends and challenges in scaling these technologies, including integrati on with existi ng electronic systems, cost-efficiency, and energy consumpti on. Finally, future directi ons are discussed, parti cularly in terms of the potenti al of quantum communicati on, the miniaturizati on of photonic devices, and the integrati on of photonics with conventi onal silicon technology, pointi ng toward a future where photonics and optoelectronics will be central to the evoluti on of communicati on and computi ng infrastructures.